Comparison of behavior between angle shear connectors with different thickness under monotonic and cyclic loadings (Gaceta Técnica, 2021)
The angle type steel connectors allow the transfer of shear effects in composite structural systems, specifically in the interaction between metal beams and reinforced concrete slabs. Studying the mechanical behavior of this type of connectors is essential due to its wide use and diffusion in construction and its low cost and easy installation on site. This article presents an experimental analysis on 16 specimens tested using the Push-Out method described by Eurocode 4, comparing 4 and 6 mm thick angular connectors arranged in 2 different positions each, exposed to monotonic and cyclic loads. The typical failure of the connectors was fracture of the base material above the weld bead. The failure in the concrete caused by the Type 2 connectors was by crushing the slabs showing noticeable cracks in relation to the Type 1 connectors that generated small cracks. Specimens with 6 mm Type 1 connectors failed due to detachment between the connectors and the slabs. Type 2 connectors were the most ductile than Type 1 connectors. The results indicate that Type 2 connectors obtained better performance in terms of ultimate shear capacity, ductility and degradation of shear stiffness. Type 1 connectors showed inferior mechanical capabilities. Finally, the experimental results were evaluated with the theoretical equations proposed by constructive codes and similar investigations
Keywords: cut connectors; angle connector; Push-Out test; loads monotonic; cyclic loads